Positioning in political marketing: How Semiotic Analysis Can Support Traditional Survey Approaches - Baines, Paul R.; Crawford, Ian; O'Shaughnessy, N. J.; Worcester, R.; Mortimore, R. (Westburn Publishers, 2014)
The 2010 British election particularly focused on the party leaders' images - a departure in fifty years of British elections. The principal contribution of the article is to illustrate how a combined approach to assessing leadership positioning using both the traditional survey and semiotic analysis can provide insights into what image attribute dimensions end up in the minds of members of the public (actual positioning) and on what image attribute dimensions party marketers are trying to position themselves (intended positioning). Using data from the 2010 British general elections, our findings indicate that the combined methodological approach would be particularly useful for brands that need repositioning, those whose image attribute positions change dramatically over time, and those who wish to target previously unresponsive target audience segments.